Surrogacy Agreement in The Perspective of Legal Sociology - Maulana, Muhamad Reza (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
This research examines the validity of surrogacy agreements in civil law and discusses surrogacy agreements in the perspective of legal sociology. The research method used is normative legal research conducted using a statute approach and conceptual approach, then analyzed qualitatively. The results of the research show that there is a problem regarding the validity of the surrogacy agreement which is considered not to meet the legal requirements of the agreement in Article 1320 of the Civil Code which is an objective requirement. The surrogacy agreement when viewed from the perspective of legal sociology will cause a social change in society based on the existence of a need where the surrogacy agreement raises pros and cons in various circles of society. In the perspective of legal sociology, the surrogacy agreement can be seen from a philosophical perspective which will cause debate in terms of ethics and morals, also seen from a pragmatic perspective where the surrogacy agreement can cause benefits for couples experiencing infertility.